Necrotizing pneumonia and purulent meningitis caused by bloodstream infection of CA-MRSA in a child: A rare case report - Li, Peng; Dai, Lizhong; Yuan, Ke; Song, Chunlan; Cheng, Yibing; Jing, Yu; Chen, Na; Cui, Junhao; Wang, Yangji; Fu, Shuqin (Frontiers in Pediatrics, 2022)
We report the case of a two-year-ten-month-old child who was admitted to our hospital due to fever for 2 days, vomiting, poor mental status for 1 day, and convulsions once.